Political Party Structure on Women's Representation in the Central Java Provincial DPRD: Evidence from 34 Provinces in Indonesia - Tri Raharjanto; Heru Rochmansjah; Arwanto Harimas Ginting; Andi Asikin (GoAcademica Research & Publishing, 2026)
Women's representation in regional legislatures remains a strategic issue in strengthening democratic quality and political inclusion in Indonesia. Although affirmative action policies have been implemented, disparities in women's representation across provinces indicate that political party structures play an important role in determining electoral outcomes. This study aims to examine the influence of political party structures on women's representation in the Provincial Regional House of Representatives (DPRD), using evidence from all 34 provinces in Indonesia, with particular attention to the implications for the Provincial DPRD of Central Java. The study employs a quantitative approach using secondary data from the 2024 legislative election and official government statistics. Multiple linear regression analysis is used to assess the effect of the electoral strength of major political parties while controlling for the Human Development Index (HDI), Female Life Expectancy (FLE), and the proportion of women employed as civil servants. The findings reveal that political party structure significantly affects women's representation in provincial legislatures. Among the major parties, the Indonesian Democratic Party of Struggle (PDI-P), Golkar, the National Awakening Party (PKB), and the National Democratic Party (NasDem) show positive associations with higher levels of women's representation. In contrast, Gerindra, the Prosperous Justice Party (PKS), the Democratic Party, the National Mandate Party (PAN), and the United Development Party (PPP) exhibit negative associations. Furthermore, the control variables, HDI, Female Life Expectancy, and the proportion of female civil servants, also contribute significantly to explaining provincial variations in women's legislative representation. These findings suggest that strengthening women's political representation requires not only affirmative policies but also more gender-inclusive party recruitment, nomination, and organizational practices. The study provides empirical evidence for improving political party institutional design to advance substantive gender equality in Indonesia's regional democratic governance.